Community structure and ecological distribution of benthic animals in Tien Hai mangrove forest, Northern Vietnam - Nhuong, Do Van; Hau, Tran Duc; Hung, Nguyen Duc; Hai, Tran Nam (Academia Journal of Biology, 2021)
Mangroves are a diverse and rich ecosystem, in which many animals are associated, including benthos. Species composition and occurrence of these animals are driven by the mangroves and tidal conditions. To examine how the benthic animal is distributed in mangrove habitats from northern Vietnam, two surveys in 2019 were conducted in Tien Hai Wetland Nature Reserve, which resulted in a total of 89 species, belonging to 56 genera and 35 families of zoobenthos. This is the first publication of these animals in the study site. The two major groups of benthic animals in the ecosystem were Crustacea and Mollusca, which occupy 54.02% and 36.78% of the total species, respectively. There are several new records of these animals from the coastal mangroves of Vietnam. Two species were new data for northern Vietnam (Scopimera curtelsoma and Parasesarma eumolpe), and four species were new records for Vietnam (Laemodonta punctigera, Cassidula nucleus, Pythia cecillei and Microtralia alba). Also, the present study shows distributional characteristics of the benthic animal community in mangrove forests. The present study indicates that benthic animals show an increase in species diversity and density from the river mouth to the continent. Seasonally quantitative data of benthic from the study site are the first work in mangrove forests of Vietnam. Recent findings are fundamental data for further studies on zoobenthos and related issues to preserve biodiversity in the mangrove forests in Vietnam.